Effect of Cooler Dialysate Temperature on Haemodynamic Stability in Hypotensive Patients on Maintenance Haemodialysis - Muhammad Umair Yasin; Malik Nadeem Azam Khan; Muhammad Iqbal; Qurat Ul Ain Azam; Muhammad Haseeb Lodhi; Ibrahim Qamar (Pakistan Armed Forces Medical Journal, 2026)
Objective: To assess the impact of lowering the dialysate temperature on the haemodynamic status of patients on maintenance haemodialysis. Study Design: Randomised Controlled Trial (IRCT trial ID 81745). Place and Duration of Study: Haemodialysis Unit, Pak Emirates Military Hospital, Rawalpindi, from September 2024 to January 2025. Methodology: Patients from both genders between 18 and 60 years old who were on twice-weeklyhemodialysis and had hypotension were included. Patients with thyroid disease, anaemia, and taking anti-hypertensive medications were excluded. The participants were randomized into two groups using an online randomization tool. The cooler dialysate group underwent cooler dialysate hemodialysis sessions, while the thermoneutral group underwent thermoneutral dialysate (37⁰C) hemodialysis sessions. During the hemodialysis session, intradialytic blood pressure and pulse rate changes were documented every hour and at the end of the session. Results: In this interventional trial, seventy (n=70) patients with 35 individuals in each group were enrolled. The median age of the participants was 54.50(46.00 -60.25) years, with 36(51.43%) males and 34(48.57%) females. The dialysis vintage was 21.00 (16.00 – 39.25) months. No significant statistical difference was observed between the cooler dialysate and thermoneutral groups regarding baseline demographic and clinical features. The systolic blood pressure increased in the intervention group at 1-hour (p=0.112) till 4-hour (p<0.001). The pulse rate showed a significant change in the intervention group in the third hour of the hemodialysis sessions (p=0.048). Conclusion: The cooler dialysate improved the hemodynamic stability in hypotensive hemodialysis-dependent patients by either maintaining or increasing blood pressure.